Fat‐Free Mass and Skeletal Muscle Mass Five Years After Bariatric Surgery. Issue 7 (30th May 2018) - Davidson, Lance E.; Yu, Wen; Goodpaster, Bret H.; DeLany, James P.; Widen, Elizabeth; Lemos, Thaisa; Strain, Gladys W.; Pomp, Alfons; Courcoulas, Anita P.; Lin, Susan; Janumala, Isaiah; Thornton, John C.; et al.
Abstract : Objective: This study investigated changes in fat‐free mass (FFM) and skeletal muscle 5 years after surgery in participants from the Longitudinal Assessment of Bariatric Surgery‐2 trial. Methods: A three‐compartment model assessed FFM, and whole‐body magnetic resonance imaging (MRI) quantified skeletal muscle mass prior to surgery (T0) and 1 year (T1), 2 years (T2), and 5 years (T5) postoperatively in 93 patients (85% female; 68% Caucasian; age 44.2 ± 11.6 years) who underwent gastric bypass (RYGB), sleeve gastrectomy, or adjustable gastric band. Repeated‐measures mixed models were used to analyze the data. Results: Significant weight loss occurred across all surgical groups in females from T0 to T1. FFM loss from T0 to T1 was greater after RYGB (mean ± SE: −6.9 ± 0.6 kg) than adjustable gastric band (−3.5 ± 1.4 kg; P < 0.05). Females with RYGB continued to lose FFM (−3.3 ± 0.7 kg; P < 0.001) from T1 to T5. A subset of males and females with RYGB and MRI‐measured skeletal muscle showed similar initial FFM loss while maintaining FFM and skeletal muscle from T1 to T5. Conclusions: Between 1 and 5 years following common bariatric procedures, FFM and skeletal muscle are maintained or decrease minimally. The changes observed in FFM and muscle during the follow‐up phase may be consistent with aging.